A hybrid active load and ideal synchronous condenser‐based model for STATCOM applied to power flow studies. Issue 4 (31st July 2019) - Karami, Ehsan; B. Gharehpetian, Gevork; Moradi CheshmehBeigi, Hassan; Rouzbehi, Kumars
Abstract : This study proposes a generalised STATCOM model employing active load and ideal synchronous condenser representation and its related power flow solution. The proposed method considers the effects of DC side voltage, internal switching losses, and operation mode on the power flow problem. To such aim, the proposed model tackles with a tap changing transformer accompanied by a variable conductance at the DC side in order to model the switching losses. This model can also take into account voltage regulation, reactive power control as well as amplitude modulation ratio and practical limitations. It is worth noting that the proposed model can be easily used for power flow studies by applying ordinary changes to the prevalent Newton–Raphson‐based power flow methods. The introduced model is applied to two test systems including IEEE 14‐Bus system, followed by a discussion on results.